AUTISM AND CREATIVITY: A SOCIAL ROBOTICS APPLICATION - Marzano, Gilberto; Zorzi, Simone (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
This paper focuses on the relationship of genius with certain forms of autism. It synthesizes some results of two ongoing research activities. The first one concerns the investigation of creativity and the arts in the digital age, while the second an educational experience to support the socialization of people with Autism Spectrum Disorder.The educational experience was based on storytelling, drama, and programmable toy robots.Our research emerged that low functioning autistic people may exhibit creative attitudes, but the creativity of educators has a crucial role in stimulating their creativity.